Impact of COVID-19 pandemic on consumer behavioural intention to purchase green products. - Ping Hu; Miraj Ahmed Bhuiyan; Muhammad Khalilur Rahman; Mohammad Mainul Hossain; Shaharin Akter (PLoS ONE, 2022)
This study examined the fear of COVID-19 pandemic and its impact on consumer behavioural intention to purchase green products. The data was collected from consumers of Malaysia in hypermarkets. A total of 491 respondents were analyzed using the partial least square technique. The results indicated that the fear of the COVID-19 epidemic has a significant impact on health concerns, social media information, intolerance of uncertainty, and personal relevance, which in turn affect consumers' behavioural intention to purchase green products. With a serial mediating effect the results identified that fear of COVID-19 epidemic is associated with behavioural intention to purchase the green product. The findings of this study are crucial for understanding the swings in the green product purchase behaviour due to the ongoing uncertainty of COVID-19 crisis.